Clinical Reasoning: Labyrinthine hemorrhage: An unusual etiology for peripheral vertigo. (10th January 2017) - Parikh, Simy K.; Frank, Samuel A.
Abstract : A 65-year-old man presented with a 2-week history of worsening vertigo. The sensation of vertigo was constant and exacerbated by turning in bed, sitting, and standing. Exacerbations lasted 5–10 minutes and were intense enough to cause gait impairment. Two days prior to presentation, the vertigo had worsened in severity and was associated with one episode of nausea and vomiting. Review of systems was positive for a 3-month history of a whistling noise in the patient's left ear, a 2-week history of acute-on-chronic left-sided hearing impairment, and a recent upper respiratory infection.